The Utilization of Wood Waste as a Handicraft Product in Londut Village, Kualuh Hulu District, Labuhan Batu Utara Regency - Meutia Nanda; Diva Aulia Natasya; M Abu Fattahillah; Ninis Lestari; Nasution, Nurul Indah (Universitas Muhammadiyah Palu, 2024)
Waste can cause environmental problems if not handled properly. This is because this waste is generally just thrown away by wood processing factories. The research problem is that wood processing produces quite large amounts of waste which can pollute the environment if not handled properly. This research aims to identify the types of wood waste produced, analyze the characteristics of the waste, and explore opportunities for utilizing wood waste in Londut Village, Kualuh Hulu District, North Labuhanbatu Regency. The research method uses a qualitative approach with interview techniques with wood craftsmen as craft owners and two craftsmen. The research results show that the main waste from wood processing is wood chips and sawdust, which are used by craftsmen and local communities to make crafts such as shoe racks, flower racks and other items. The existence of wood processing actually has a positive impact on society, such as ease of obtaining building materials and additional sources of income. In conclusion, the use of wood waste in Londut Village has been carried out well and provides economic benefits for the surrounding community. Suggestions for utilizing wood processing waste in Londut Village, namely education and training for wood craftsmen on sustainable waste management practices are very important to increase their knowledge and skills.